Determinants of Credit Growth in Commercial Banks in Indonesia - LOISSA, Angelica Febbryana; KRISNANDA, Gede Harry (PT Keberlanjutan Strategis Indonesia, 2023)
Banks have a very vital task in maintaining the Indonesian economy. One of the main tasks of banks is to collect and distribute public funds. Banks channel public funds through loans that get rewards in the form of loan interest. This research focuses on studying what factors affect the amount of credit in the long run. This study uses deposits, lending rates (SBK), non-performing loans (NPL), GDP growth, inflation as internal and external factors that affect the amount of lending to commercial banks. The results showed that partially deposits had a negative and significant effect, NPL had a negative and significant effect, SBK had a negative but insignificant effect, GDP growth had a positive and significant effect and inflation had a positive but insignificant effect on the amount of lending to commercial banks in Indonesia. While simultaneously deposits, loan interest rates (SBK), non-performing loans (NPL), GDP growth, inflation have a significant effect on the amount of lending to commercial banks in Indonesia in 2012-2019.